Precautions and Recommendations for Dental Care During the COVID-19 Pandemic - Borja de Melo, Téssia Richelly Nóbrega; Costa, Poliana de Santana; de Sousa Medeiros, Rafaela Araújo; Araújo-Filho, Jorge Luiz Silva; de Oliveira Júnior, Augusto Garcia (The Journal of Dentists, 2020)
The COVID-19 disease pandemic, caused by the new Coronavirus (SARS-COV-2) that originated in Wuhan, China, is an international public health emergency. This disease represents a major challenge for all health professionals, including dentists and their staff. This moment has significantly changed the attendance and routine of dental offices, so there is a great need for information and the development of protocols for the guidance of professionals. This paper aims to systematize the recommendations for dentists’ clinical practice on biosafety and the use of Personal Protective Equipment (PPE), seeking to optimize dental care during the COVID-19 pandemic.